Defining solute carrier transporter signatures of murine immune cell subsets - Aaes, Tania Løve; Burgoa Cardás, Javier; Ravichandran, Kodi S. (Frontiers in Immunology, 2023)
Solute carrier (SLC) transporters are membrane-bound proteins that facilitate nutrient transport, and the movement across cellular membranes of various substrates ranging from ions to amino acids, metabolites and drugs. Recently, SLCs have gained increased attention due to their functional linkage to innate immunological processes such as the clearance of dead cells and anti-microbial defense. Further, the druggable nature of these transporters provides unique opportunities for improving outcomes in different immunological diseases. Although the SLCs represent the largest group of transporters and are often identified as significant hits in omics data sets, their role in immunology has been insufficiently explored. This is partly due to the absence of tools that allow identification of SLC expression in particular immune cell types and enable their comparison before embarking on functional studies. In this study, we used publicly available RNA-Seq data sets to analyze the transcriptome in adaptive and innate immune cells, focusing on differentially and highly expressed SLCs. This revealed several new insights: first, we identify differentially expressed SLC transcripts in phagocytes (macrophages, dendritic cells, and neutrophils) compared to adaptive immune cells; second, we identify new potential immune cell markers based on SLC expression; and third, we provide user-friendly online tools for researchers to explore SLC genes of interest (and the rest of the genes as well), in three-way comparative dot plots among immune cells. We expect this work to facilitate SLC research and comparative transcriptomic studies across different immune cells.